Science didactics of mathematics in Lithuania: Quo vadis? - Narkevičienė, Bronė; Novikienė, Regina (Lietuvos matematikos rinkinys, 2018)
The article presents the results of the analysis of the science didactics of mathematics situation at the state, social and institutional levels, and recommendations for improvement of the situation is given.